Racismo e xenofobia nas escolas estaduais e municipais da cidade de São Paulo - Silva, Andrew Souza (2024)
This thesis aims to analyze the insertion, permanence and reception of black immigrant students in the public educational system offered by state and municipal schools in the city of São Paulo. Brazil has registered an increase of several situations and cases of hate crimes, among them xenophobia and racism. These practices that have historically been present in the daily social relations of the country, do not leave out the school environment and reflect the prejudices socially anchored in the colonial past since the sixteenth century. The choice of school units spread across different regions of the city was precisely to know and analyze the different proposals and actions carried out by the teaching boards (municipal and state) of which the schools are subordinated. We conducted field research during the years 2022 and 2023 in the eight school units: CEU EMEF Perus and E.E. Manuel Bandeira, belonging to the northern region, EMEF Antônio Alves da Silva (Sg.) and E.E. Prof. João Silva, belonging to the southern region, CEU EMEF Antônio Carlos Rocha (Prof.) and E.E. Dom João Maria Ogno Osb located in the eastern region, EMEF Duque de Caxias and E.E. Paulo Luig located in the central region. From this premise we intend, thus, to answer the main question of the thesis: - "How is the Education and the interaction of the black immigrant student in the teaching units of the state and municipal networks of the city of São Paulo”. The research is qualitative and quantitative and the methodological route is the use of a questionnaire with open and closed questions for teachers, management team and students, as well as field study, ethnography, literature review, publications relevant to the theme in the area of Applied Social Sciences, the analysis of the Official Documents of the eight teaching units and Laws nº10.639/2003, nº11.645/2008, nº16.478/2016 and nº7.716/1989. The study is organized in Presentation that brings the personal and professional trajectory of the researcher until his entry in the doctorate, Introduction that addresses the importance of conducting the research, the development of the theme, and four chapters that materialize the results of the research, the first chapter entitled "The Black and Education", the second chapter, "Immigration: racism, prejudice and xenophobia", the third chapter, "Immigrants in the Public Educational Network of the City of São Paulo", the fourth and final chapter, "Research Data: racism and xenophobia in school" and the final considerations in which are recorded the main contributions of this work and some concerns arising from the interpretation and completion of the research that confirms the existence of racist attitudes, prejudiced and xenophobic towards immigrant students and others. This research contributes to analyze and reflect on how Laws nº10.639/2003 and nº16.478/2016 are being implemented, the teaching for and on immigrant peoples and other guidelines elaborated both by the State, as by the City of São Paulo in its search for alternatives of pedagogical practices aimed at a proposal of anti-racist education in educational institutions, so that there is constancy in the process of reflectionaction when dealing with and living with multiple differences